Artificial synapses that exploit ionic modulation for perception and integration. (May 2021) - Wei, H.; Han, H.; Guo, K.; Yu, H.; Gong, J.; Ma, M.; Ni, Y.; Feng, J.; Xu, Z.; Xu, W.
Abstract: We propose the first two-terminal sodium-ion artificial synapse (SIAS) with nanoparticle/electrolyte architecture to emulate behaviors of a biological synapse. The device emulates essential synaptic functions such as postsynaptic current and paired-pulse facilitation by employing sodium-ion doping. The synaptic event uses only 0.55 pW at an ultra-low operating voltage of −6 mV, sensitive responsiveness. Pain perception nociceptors, with pain sensitization/desensitization properties, are realized using SIAS. Artificial neural components with multiple inputs also implement dendritic integration functions such as spatiotemporal learning rules and classical conditional learning. Furthermore, benefiting from the nanostructured active layer and solid-state polymer electrolyte, the flexible device on stainless steel substrate induced different deformation curvatures. The proposed SIAS device with capabilities of parallel information processing and pain perception could apply to future bioinspired flexible sensing-processing nervous systems. Graphical abstract: Image 1 Highlights: The two-terminal sodium ion artificial synapse was designed and fabricated to mimic biological signal transmission. The synaptic device exhibits millivolt sensitive voltage responsibility and ultra-low power consumption. Several interesting dendritic integration projects were emulated. The synapse on a flexible substrate endured different degrees of bending.